Lean Manufacturing in a South African - Rider, Ryan (My University, 2011)
Even though lean manufacturing has been around for many years it is still influencing how vehicle manufacturers conduct their business. Customer demand on customization is becoming a big influencing factor in how motor manufacturers evolve into the future, and with the amount of models available the customer is becoming spoilt for choice putting pressure onto the manufacturers to customize as much as possible but still not increase costs. In today’s competitive market, companies have had to find ways of reducing costs and maximizing profits. BMW realized the way they design and produce cars was far too expensive and that the Japanese could do it much better, by producing high quality with low cost. The purpose of this research is to evaluate how successful and sustainable lean manufacturing has been at BMW South Africa. An extensive literature survey was carried out on this subject. Qualitative research was conducted through an interview process to investigate how successful BMW South Africa has been in implementing lean manufacturing. The results suggest that BMW have been quite successful in implementing lean manufacturing within their manufacturing division, but less successful in other areas of the business. The results also show that the success and sustainability of lean manufacturing at BMW is very reliant on leadership involvement and that communication and team work have been vital to its success. The results also suggest that BMW South Africa is at the moment more focused on reducing costs than on increasing flexibility. This could be as a result of their limitation of producing only one variant within the model lineup. Even though BMW has shown moderate success in a short amount of time a lot of work remains before they can be considered a truly lean organization
MBA - WBS
Keywords: Lean manufacturing; Automotive manufacturers; Motor car manufacturers; Car manufacturers